Evaluation of rice husk biochar influence as a partial cement replacement material on the physical, mechanical, microstructural, and radiation shielding properties of ordinary concrete - Alaa A. Mahmoud; Alaa A. El-Sayed; Islam N. Fathy; Samer Fawzy; Mansour Alturki; Maged E. Elfakharany; Mohamed A. Abouelnour; K. A. Mahmoud; Hany A. Dahish; Soliman M. ElTalawy; Islam M. Nabil (Scientific Reports)
Abstract This study investigated the viability of rice husk-derived biochar (RHB) as a partial substitute for cement in concrete. The used RHB, characterized by a novel chemical composition abundant in silicon and aluminum oxides, was incorporated into ordinary concrete at increasing substitution ratios up to 25% by cement weight. A comprehensive evaluation was conducted to assess the influence of RHB on various properties of concrete, including physical (setting time, standard consistency, workability), mechanical (compressive and tensile strength), microstructural (XRD, and EDX), and radiation shielding characteristics. The results indicated that RHB marginally increased cement setting time, with a maximum 7.14% increase observed at a 25% replacement level. However, it significantly increased water demand for standard consistency, reaching 35.7% at 25% replacement. The increased water demand correlated with a reduction in workability, with a maximum slump reduction rate of 57.3% at a 25% replacement level. The optimal replacement levels for mechanical strength enhancement were at 10% for compressive strength and 15% for tensile strength, achieving improvements of 13.74% and 9.48%, respectively. Additionally, Monte Carlo simulation code and PhyX software were employed for assessing gamma and fast neutron radiation attenuation characteristics of concrete. Gamma-ray attenuation tests revealed moderate improvements in the concrete’s gamma-ray shielding capacity. Interestingly, the 15% RHB sample demonstrated a higher linear attenuation compared to the other samples, a result of its increased density. On the contrary, the 25RHB sample is less valuable. The 15RHB sample had the highest value for FCS (0.090 cm−1) indicating its efficacy as a neutron shield.